Genômica populacional do Mico-Leão-Preto (Leontopithecus chrysopygus, Mikan 1823): uma espécie ameaçada de extinção - Ayala Burbano, Paola Andrea (Universidade Federal de São Carlos, 2021)
The species Leontopithecus chrysopygus, endemic to the Atlantic Forest of the state of São Paulo, is considered endangered by the IUCN and IBAMA. It is estimated that currently the free-living population of this species does not exceed 1500 animals. In captivity, there are just over 50 individuals, which have difficulty reproducing, a fact that has contributed to the population decline and increase in inbreeding levels. Priority actions for the conservation of this species known as black lion tamarin (MLP) have highlighted the importance of studies that expand the knowledge about genetic diversity in forest fragments with different degrees of alteration. This knowledge is especially relevant to assist the monitoring and management of wild populations, as well as captive groups, which constitute an important source for conservation programs, but need to renew their stocks. Overall, with the objective of contributing to the Black Lion Tamarin Conservation Program and the National Action Plan for the Conservation (PAN) of Primates of the Atlantic Forest, first we carried out integrated pedigree and microsatellites analyzes to infer demographic and genetic diversity parameters, and assess the genetic structure of captive groups of the species. Next, a systematic literature review was carried out to gather and raise relevant information about ecology, behavior, genetics, and conservation of black lion tamarin populations in different landscapes. Finally, we examined neutral and non-neutral genetic diversity and investigated putative signals of differential selection in wild populations using single nucleotide polymorphisms (SNPs) prospected by sequencing genotyping (GBS) of next generation data. In addition, we determine the degree of relatedness and characterize the genetic structure of populations based on the identified SNPs. The methodology used and the main results regarding the approaches used and their implications are presented and discussed in this thesis in three chapters organized as scientific articles.
Population genomics of the Black Lion Tamarin (Leontopithecus chrysopygus, Mikan 1823): an endangered species
Keywords: Mico-leão-preto; Genômica da conservação; Diversidade genética; Adaptação; Seleção; SNPs; Studbook; Ecology; Behavior; Genotyping by sequencing; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::GENETICA